Ternary compound magnetic material as well as preparation method and application thereof

By mixing Pr and Dy with Co, the ternary compound Pr1-xDyxCo5 is prepared, and the high-speed single-roll melt belt swing method is used to solve the problem of weak magnetic properties of PrCo5 and DyCo5, which is effective in preparing high-performance nanocrystalline magnets, reducing costs And improves magnetic performance.

CN119314767AActive Publication Date: 2025-01-14GUILIN UNIV OF ELECTRONIC TECH +1
View PDF 7 Cites 0 Cited by

Patent Information

Application Number
CN202411366044.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-29
Publication Date
2025-01-14
Estimated Expiration
2044-09-29

AI Technical Summary

Technical Problem

The existing PrCo5 and DyCo5 binary compounds have weak magnetic properties, long preparation period, high cost, and are not effectively used in the field of high-temperature magnets.

Method used

Mix light rare earth Pr and heavy rare earth Dy with transition metal Co to prepare ternary compound Pr1-xDyxCo5, and use high-speed single-roll melt belt swing method to obtain nano-sized magnetic strip material. By adjusting process conditions such as wheel speed and heat treatment time, it is maintained. 1:5 CaCu5 type rhombus square phase structure.

Benefits of technology

It significantly improves the magnetic properties of ternary compounds, reduces the cost of rare earth separation, shortens the preparation time, and obtains nanocrystalline materials with high coercive force and high saturation magnetization, suitable for high temperature magnet applications.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119314767A_ABST
    Figure CN119314767A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of magnetic material preparation, in particular to a ternary compound magnetic material and a preparation method and application thereof. The chemical formula of the ternary compound magnetic material is Pr < 1-x > DyxCo < 5, 0 lt >, xlt; the ratio of the total atom number of Pr and Dy to the atom number of Co is 1: 5. The coercive force of the ternary compound magnetic material is remarkably enhanced compared with that of PrCo5 and DyCo5 binary compounds, the extraction and separation cost of rare earth Pr and Dy in primary ore can be reduced, the weak magnetism of the PrCo5 and DyCo5 binary compounds is changed, and the coercive force is remarkably improved. Compared with a magnetic alloy with the same components, the ternary magnetic strip provided by the invention has larger coercive force and better magnetic performance, and the coercive force enhancement phenomenon is more obvious. The method is simple in process and easy to prepare, the cost is reduced, and application of the high-performance magnet in more permanent magnet devices is facilitated.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of magnetic material preparation, and in particular to a ternary compound magnetic material and a preparation method and application thereof. Background Art

[0002] Since its discovery in the late 1960s, rare earth cobalt-based magnetic materials (RCM) have been widely used in commercial and scientific fields. The most commonly used alloy of RCM materials is the 1:5 rare earth cobalt permanent magnet alloy SmCo5. Compared with NdFeB materials, RCM materials have irreplaceable properties at high temperatures. In recent years, the research on RCM has mainly focused on obtaining high coercivity (H) while working at high temperatures. c ), high saturation magnetization (M s ) and high magnetic energy product (BH). For example, the (Sm, Pr) Co5 permanent magnet alloy obtained by replacing part of the Sm in the SmCo5 alloy with light rare earth Pr is intended to increase the maximum magnetic energy product of the alloy. Because the theoretical value of the saturation magnetization intensity of PrCo5 is higher than that of SmCo5, but the addition of praseodymium reduces the anisotropy field, the coercive force of the alloy is lower than that of SmCo5. For another example, the MMCo5 permanent magnet alloy ("MM" is the abbreviation of Ce-rich mixed rare earth metal). The use of mixed rare earths is mainly to reduce costs, but the magnetic energy product of the alloy decreases with the addition of Ce elements and is easily oxidized. Another example is the (Sm, HRE) Co5 permanent magnet alloy. This type of alloy replaces part of the Sm in SmCo5 with heavy rare earth elements such as Gd, Ho and Er (abbreviated as HRE). The purpose is to improve the temperature stability of the magnet, but after increasing the content of HRE, the magnetism decreases and the cost increases. For another example, R(CoCuFe) 5~7 (R=Sm, Ce) permanent magnet alloy. This type of alloy is based on RCo5 alloy with Fe and Cu replacing part of Co. The maximum magnetic energy product is slightly lower, but the coercive force is much lower.

[0003] Based on the research on SmCo5 materials, it is found that the combination of rare earth and transition metal can obtain high-performance permanent magnets. Among them, transition metal provides high Curie temperature (T c ) and saturation magnetic moment, and rare earth atoms have large uniaxial anisotropy, which can make the magnet have a large coercive force. In recent years, in order to find materials without Sm, other RCo5 system compounds are still under continuous research. Rare earth permanent magnet PrCo5 has high saturation magnetization, relatively large uniaxial anisotropy field, large theoretical magnetic energy product and high Curie temperature, such as T of PrCo5. c (950K) higher than Nd2Fe 14 B of T c(571K), it is possible to produce magnets with higher magnetic properties and temperature stability, so it is a potential candidate for high-performance magnets. However, due to the easy generation of impurity phases and other factors during the preparation process, PrCo5 has not been practically applied in production.

[0004] Currently, the reported magnetic properties of the binary compound PrCo5 are average and do not show the application value of strong magnetic magnets; in addition, the magnetic properties of the binary compound DyCo5 also show average performance, and its magnetic properties are far inferior to those of other magnetic materials, so it has not attracted people's attention. Therefore, these single binary compounds have not been developed and applied. Summary of the Invention

[0005] To solve the above problems, the present invention provides a ternary compound magnetic material, its preparation method and application. The present invention designs to mix the light rare earth Pr, the heavy rare earth Dy and the transition element Co to prepare the ternary Pr 1-x Dy x Co5 compound, and then use the thin strip sample prepared by high-speed single-roll melt spinning. The crystal structure always maintains the CaCu5-type rhombohedral phase of 1:5. This method can not only reduce the separation cost of rare earth Pr and Dy, but also significantly improve the magnetic properties of both PrCo5 and DyCo5. The present invention develops a ternary composite magnet (Pr, Dy)Co5. By changing the process conditions, the ternary compound Pr 1-x Dy x Co5 magnetic strip is prepared by melt spinning at a wheel speed of 30 - 35 m / s. Melt quenching can obtain samples with nanometer size. Nanocrystalline materials are one of the key research fields of permanent magnets in the past decade because nanograin magnets can generate very high coercivity.

[0006] To achieve the above object, the present invention provides the following technical solutions:

[0007] The present invention provides a ternary compound magnetic material, and the chemical formula of the ternary compound magnetic material is Pr 1-x Dy x Co5, 0 < x < 1, and the ratio of the total number of atoms of Pr and Dy to the number of atoms of Co is 1:5.

[0008] Preferably, the x is 0.2 - 0.8.

[0009] Preferably, the x is 0.4 - 0.6.

[0010] The present invention also provides a preparation method of the ternary compound magnetic material described in the above technical solution, including the following steps:

[0011] 1) Mix the Pr, Dy and Co and then melt them to obtain an alloy;

[0012] 2) heat-treating the alloy obtained in step 1) to obtain a heat-treated product;

[0013] 3) placing the heat-treated product obtained in step 1) in an ice-water mixture until the temperature is constant, and then soaking the mixture to obtain a ternary compound magnetic material.

[0014] Preferably, the smelting conditions in step 1) include: repeating 4 to 6 times under argon protection and an arc current of 80 to 120 A.

[0015] Preferably, the heat treatment conditions in step 2) include: a temperature of 750 to 800° C. and a time of 2 h to 7 d.

[0016] Preferably, the soaking time in step 3) is 0.5 h.

[0017] Preferably, the alloy obtained in step 2) is subjected to belt spinning treatment and then heat treatment, and the conditions of the belt spinning treatment include: being carried out under argon protection and a roller speed of 30 to 35 m / s.

[0018] The present invention also provides the use of the ternary compound magnetic material described in the above technical solution in improving the coercive force of magnetic materials.

[0019] The present invention also provides the application of the ternary compound magnetic material described in the above technical solution in improving the magnetic properties of magnetic materials.

[0020] Beneficial effects of the present invention:

[0021] The present invention addresses the problems of weak magnetic properties, long preparation cycle and high cost in existing PrCo5 and DyCo5 binary intermetallic compounds. Compared with single PrCo5 and DyCo5 binary compounds, the mixed addition of light and heavy rare earths not only reduces the cost of rare earth separation, but also significantly improves the magnetic properties of the synthesized ternary compound (Pr, Dy) Co5. The preparation method of melt quenching significantly improves the material properties while shortening the preparation time. Alloy and thin strip samples can obtain nano-sized grains after appropriate heat treatment. Changing the process conditions can maximize the improvement of magnetic properties. The cobalt-based compound obtained by adding heavy rare earth Dy to PrCo5 has better magnetic properties, further reducing costs, which is of great significance to relieving resource pressure and sustainable development of resources. BRIEF DESCRIPTION OF THE DRAWINGS

[0022] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required to be used in the embodiments are briefly introduced below.

[0023] Figure 1 Pr 1-x Dyx Magnetic hysteresis loop of Co5 (x = 0.0-1.0) alloy at room temperature after annealing at 800 °C for 7 days;

[0024] Figure 2 Pr 1-x Dy x Co5 (x = 0.0-1.0) alloy annealed at 800 ° C for 7 days at room temperature and the coercive force and saturation magnetization intensity change diagram;

[0025] Figure 3 Pr obtained at 30m / s 1-x Dy x Single-phase XRD pattern of Co5 (x = 0.0-1.0) ribbon after annealing at 750 °C for 4 h;

[0026] Figure 4 Pr obtained at 30m / s 0.8 Dy 0.2 Morphology of Co5 ribbon annealed at 750℃ for 4h;

[0027] Figure 5 Pr obtained at 30m / s 1-x Dy x Magnetic hysteresis loop of Co5 (x = 0.0-1.0) ribbon at room temperature after annealing at 750℃ for 4h;

[0028] Figure 6 Pr obtained at 30m / s 1-x Dy x Coercivity and saturation magnetization of Co5 (x = 0.0-1.0) ribbon after annealing at 750 ° C for 4 hours;

[0029] Figure 7 Unheat-treated Pr prepared at 35 m / s 1-x Dy x Magnetic hysteresis loop of Co5 (x = 0.0-1.0) ribbon at room temperature;

[0030] Figure 8 Unheat-treated Pr prepared at 35 m / s 1-x Dy x Coercivity and saturation magnetization of Co5 (x = 0.0-1.0) ribbon at room temperature;

[0031] Fig. 9 Pr obtained at 35m / s 1-x Dy x Magnetic hysteresis loop of Co5 (x = 0.0-1.0) ribbon at room temperature after annealing at 800℃ for 2h;

[0032] Fig.10Pr prepared at 35 m / s 1-x Dy x Variation diagram of coercivity and saturation magnetization of Pr 1-x Dy x Co5 (x = 0.0 - 1.0) ribbon annealed at 800 °C for 2 h;

[0033] Fig.11 Pr 1-x Dy x Variation diagram of coercivity of Pr 1-x Dy x Co5 (x = 0.0 - 1.0) samples under different states, different spinning speeds and different heat treatment conditions. Specific implementation mode

[0034] The present invention provides a ternary compound magnetic material, and the chemical formula of the ternary compound magnetic material is Pr 1-x Dy x Co5, 0 < x < 1, and the ratio of the total atomic number of Pr and Dy to the atomic number of Co is 1:5. In the present invention, the x is preferably 0.2 - 0.8. In the present invention, the x is preferably 0.4 - 0.6.

[0035] The present invention also provides a preparation method of the ternary compound magnetic material described in the above technical solution, including the following steps:

[0036] 1) Mix Pr, Dy and Co and melt them to obtain an alloy;

[0037] 2) Heat-treat the alloy obtained in step 1) to obtain a heat-treated product;

[0038] 3) Place the heat-treated product obtained in step 1) in an ice-water mixture until it reaches a constant temperature, and then soak it to obtain a ternary compound magnetic material.

[0039] In the present invention, Pr, Dy and Co are mixed and melted to obtain an alloy. In the present invention, the melting conditions preferably include: repeating 4 - 6 times under argon protection and an arc current of 80 - 120 A.

[0040] In the present invention, the obtained alloy is heat-treated to obtain a heat-treated product. In the present invention, the heat-treatment conditions preferably include: a temperature of 750 - 800 °C and a time of 2 h - 7 d.

[0041] In the present invention, the obtained heat-treated product is placed in an ice-water mixture until it reaches a constant temperature, and then soaked to obtain a ternary compound magnetic material. In the present invention, the soaking time is preferably 0.5 h.

[0042] ​​​​The present invention preferably performs a belt-spinning treatment on the obtained alloy and then performs a heat treatment, and the belt-spinning treatment preferably includes: performing the treatment under argon protection and a roller speed of 30 to 35 m / s. The present invention preferably melts the alloy into a liquid state under a chamber pressure of 0.04 to 0.06 MPa and argon protection, and then performs a belt-spinning treatment.

[0043] The present invention also provides the use of the ternary compound magnetic material described in the above technical solution in improving the coercive force of magnetic materials.

[0044] The present invention also provides the application of the ternary compound magnetic material described in the above technical solution in improving the magnetic properties of magnetic materials.

[0045] In order to further illustrate the present invention, the present invention is described in detail below in conjunction with embodiments, but they should not be construed as limiting the scope of protection of the present invention.

[0046] Example 1

[0047] A method for preparing a magnetic material with enhanced coercivity comprises the following steps:

[0048] Step (1): according to the ratio of rare earth to Co atoms of 1:5, weigh the rare earth Pr, Dy and raw material Co, and use the argon arc melting method (repeatedly melt 4 times with a current of 100A) to prepare Pr 1-x Dy x Co5 (x = 0.0-1.0) alloy, wherein x is 0, 0.2, 0.4, 0.6, 0.8 and 1;

[0049] Step (2): Pr prepared in step (1) 1-x Dy x Co5 (x = 0.0-1.0) alloy was sealed in a vacuum quartz tube, placed in an annealing furnace at 800 ° C for 7 days, and then placed in an ice-water mixture to quickly cool to room temperature and soak for half an hour to obtain Pr 1-x Dy x Co5 (x = 0.0-1.0) samples.

[0050] In order to test the hysteresis loop of the sample at room temperature, the magnetic properties of the sample were tested using a vibrating sample magnetometer (VSM). The specific method is as follows:

[0051] Select a 20 mg sample and apply a maximum external magnetic field of ±2 T to 1-x Dy x The Co5 (x = 0.0-1.0) sample was placed parallel to the external magnetic field. The test results showed that its magnetic moment had reached saturation under ±2T external magnetic field. Figure 1As shown; the coercive force shows a trend of increasing first and then decreasing. The coercive forces at x = 0.0, 0.2, 0.4, 0.6, 0.8, and 1.0 are 0.085, 0.157, 0.200, 0.196, 0.195, and 0.187 kOe, respectively; the maximum value of 0.20 kOe is obtained at x = 0.4, and the saturation magnetization shows a downward trend with the increase of the heavy rare earth Dy content, as shown Figure 2 .

[0052] Example 2

[0053] A method for preparing a magnetic material with enhanced coercivity comprises the following steps:

[0054] Step (1): weigh the raw materials according to the ratio of rare earth and Co atoms being 1:5, and use argon arc melting to prepare Pr 1-x Dy x Co5 (x = 0.0-1.0) alloy, wherein x is 0, 0.2, 0.4, 0.6, 0.8 and 1;

[0055] Step (2): Pr prepared in step (1) 1-x Dy x The Co5 (x=0.0-1.0) alloy was rapidly cooled into a thin strip at a roller speed of 30 m / s in an induction melting and spinning device in an argon environment.

[0056] Step (3): The thin strip Pr prepared in step (2) at 30 m / s 1-x Dy x The Co5 (x = 0.0-1.0) sample was sealed in a vacuum quartz tube and placed in an annealing furnace at 750 ° C for 4 hours. After the heat treatment, it was placed in an ice-water mixture and quickly cooled to room temperature and soaked for half an hour to obtain Pr 1-x Dy x Co5 (x = 0.0-1.0) samples.

[0057] In order to detect the composition and structure of the samples, X-ray diffraction tests were carried out. 1-x Dy x The X-ray results of Co5 (x = 0.0-1.0) samples are as follows Figure 3 As shown, it shows a single-phase crystal structure of CaCu5 type rhombohedral. In order to verify that the sample is a single-phase structure, a thin strip sample was selected, corroded with metallographic etching solution, wiped clean with alcohol, and observed under a scanning electron microscope (SEM). 0.8 Dy 0.2 The morphology of the Co5 ribbon is as follows Figure 4 As shown, the SEM image shows that the sample has only one phase. 1-x Dy xThe magnetic properties of Co5 (x = 0.0-1.0) permanent magnet materials, such as Figure 5 As shown, the coercive force shows a trend of increasing first and then decreasing. The coercive forces at x = 0.0, 0.2, 0.4, 0.6, 0.8, and 1.0 are 2.80, 4.55, 3.38, 2.28, 0.53, and 0.11 kOe, respectively; the maximum value of 4.55 kOe is obtained at x = 0.2, and the saturation magnetization shows a downward trend with the increase of the heavy rare earth Dy content, as shown in Figure 6 .

[0058] In order to demonstrate the effect of belt spinning speed on material properties, Examples 3 and 4 are provided, that is, samples with the same composition are prepared, and the belt spinning speed is 35 m / s. 1-x Dy x Co5 (x=0.0-1.0) permanent magnet material.

[0059] Example 3

[0060] A method for preparing a magnetic material with enhanced coercivity is not described, and is the same as Example 2, except that the strip spinning speed used in step (3) is 35 m / s, the strip is rapidly cooled into a thin strip, and no other heat treatment is performed.

[0061] Measured Pr 1-x Dy x The magnetic properties of Co5 (x = 0.0-1.0) permanent magnet materials, such as Figure 7 As shown, the coercive force shows a trend of increasing first and then decreasing. The coercive forces at x = 0.0, 0.2, 0.4, 0.6, 0.8, and 1.0 are 3.46, 4.43, 4.03, 3.10, 0.72, and 0.26 kOe, respectively; the maximum value of 4.43 kOe is obtained at x = 0.2, and the saturation magnetization shows a downward trend with the increase of the heavy rare earth Dy content, as shown in Figure 8 .

[0062] Example 4

[0063] A method for preparing a magnetic material with enhanced coercivity is not described, and is the same as that of Example 2, except that the strip-spinning speed used in step (3) is 35 m / s, and the obtained strip-shaped Pr 1-x Dy x The Co5 (x = 0.0-1.0) sample was sealed in a vacuum quartz tube, placed in an annealing furnace at 800 ° C for 2 h, and then placed in an ice-water mixture to quickly cool to room temperature and soak for half an hour to obtain Pr 1-x Dy x Co5 (x = 0.0-1.0) material.

[0064] Measured Pr 1-x Dy xThe magnetic properties of Co5 (x = 0.0-1.0) permanent magnet materials, such as Fig. 9 As shown, the coercive force shows a trend of increasing first and then decreasing. The coercive forces at x = 0.0, 0.2, 0.4, 0.6, 0.8, and 1.0 are 4.19, 11.27, 6.11, 3.21, 0.54, and 0.26 kOe, respectively; the maximum value of 11.27 kOe is obtained at x = 0.2, and the saturation magnetization shows a downward trend with the increase of the heavy rare earth Dy content, as shown in Fig.10 .

[0065] By comparing the examples 2, 3 and 4, it can be proved that the hub speed during belt throwing has an important influence on the permanent magnetic properties of the material. When the roller speed is 35 m / s and after a certain heat treatment, the coercive force of the material is 11.27 kOe, which is the highest among the Pr 1-x Dy x The maximum coercivity obtained for Co5 (x = 0.0-1.0) material. Currently, the optimal roller speed for this material is 35 m / s. It is found that the samples prepared at higher belt speeds have higher coercivity. 1-x Dy x Comparison of the coercivity of Co5 (x = 0.0-1.0) ribbon samples under different states, different spinning speeds, and different heat treatment conditions, such as Fig.11 As can be seen from the figure, after Dy is added to the PrCo5 binary compound to form a ternary compound, the coercive force shows a significant enhancement effect with the increase of the added amount x, which is very useful for developing and improving the coercive force and magnetic properties of magnetic materials, and its application will be comprehensively improved.

[0066] Although the above embodiment describes the present invention in detail, it is only a part of the embodiments of the present invention, not all of the embodiments. People can also obtain other embodiments based on this embodiment without creativity, and these embodiments all fall within the protection scope of the present invention.

Claims

1. A ternary compound magnetic material, characterized in that: The chemical formula of the ternary compound magnetic material is Pr 1- x Dy x Co5, where 0 < x < 1, and the ratio of the total atomic number of Pr and Dy to the atomic number of Co is 1:

5.

2. The ternary compound magnetic material according to claim 1, characterized in that: The x is 0.2 to 0.

8.

3. The ternary compound magnetic material according to claim 2, characterized in that: The x is 0.4 to 0.

6.

4. A method for preparing the ternary compound magnetic material according to any one of claims 1 to 3, characterized in that: The following steps are involved: 1) mixing the Pr, Dy and Co and smelting them to obtain an alloy; 2) heat-treating the alloy obtained in step 1) to obtain a heat-treated product; 3) placing the heat-treated product obtained in step 1) in an ice-water mixture until the temperature is constant, and then soaking the mixture to obtain a ternary compound magnetic material.

5. The ternary compound magnetic material according to claim 4, characterized in that: The smelting conditions of step 1) include: repeating 4 to 6 times under argon protection and an arc current of 80 to 120A.

6. The ternary compound magnetic material according to claim 5, characterized in that: The conditions of the heat treatment in step 2) include: a temperature of 750 to 800° C. and a time of 2 h to 7 d.

7. The ternary compound magnetic material according to claim 5, characterized in that: The soaking time in step 3) is 0.5 h.

8. The ternary compound magnetic material according to claim 5, characterized in that: The alloy obtained in step 2) is subjected to belt spinning treatment and then heat treatment. The belt spinning treatment is carried out under argon protection and a roller speed of 30 to 35 m / s.

9. Use of the ternary compound magnetic material according to any one of claims 1 to 3 in improving the coercive force of magnetic materials.

10. Use of the ternary compound magnetic material according to any one of claims 1 to 3 in improving the magnetic properties of magnetic materials.

Citation Information

Patent Citations

  • Preparation method of samarium-cobalt (SmCo) system sintered materials

    CN102651263A

  • High-temperature-stability permanent magnet material and application thereof

    CN107123497A

  • Permanent magnet material and preparation method thereof

    CN114512288A

  • Quick quenching method for preparing anisotropic permanent-magnet Sm-Co materials

    CN1274015A

  • Prepn process of anisotropic permanent magnetic thin RCo5 belt

    CN1403606A